(3QSGdI GdNd GdfGUM aj Md GdeTcd GdhGVMs - (3HQgGf GdOjf CHh ESMGb EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdLYHQj,J (B732 (3g` s ((3eOQSI GdfhQjI (B/ (3HeOjfI HYdHc s)
(3ChdgG (B:s
(3hHYO agPg QSGdI Edi HYV GdENhGf ef Cgd GdbQBf QGaYI dgPg GdhGbYI GdTfjYI hGdHOYI GdaVjYI eHjfI deG UMa ebheI deG MQa hgh Gf bhekG ef GdbQGA hZjQge s
(3BNQgG (B:s
(3abdJ dHYV CUMGHg eG SHH gPg bGd di eG eYfGg Yde eG CfJ Ydjg ef GdaVd ChGdEaGOI aCcQec hCQLhG Cf jchf Pdc HTQi ddChdi HGdUhGH , hGdGNQi HMSf GdeBH s
(3ai GdQO Ydi ef Sei ZjQ GdbQGAGJ GdSHYI ef GdTGPs
(3YdjgG ELGRI HNW GdeDda dCMeO Hf EHQGgje Hf UGHQ GdHYdi hgh GdfGSNs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B14s
Keywords: (3GdbQGAGJ hGdJLhjOs